Enhancing Vocabulary Learning in Diverse EFL Classrooms: Integrating PPP Method with Pear Deck and Flashcard Factory - Khaerani, Nadya Shifa; Amri, M. Misbahul; Setyowati, Lestari (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study aimed to examine the effectiveness of integrating Pear Deck and the Flashcard Factory features with the Presentation, Practice, and Production (PPP) method in enhancing students’ vocabulary skills in a mixed-ability classroom. The study employed a mixed-methods design with 36 students from two mixed-ability classes at PKBM (Community Service). Quantitative data were collected using a quasi-experimental method, which relied on pre- and post-test results, and analyzed with t-tests and descriptive statistics in SPSS. The results showed that the experimental group experienced a significant increase in vocabulary mastery, with a rise of 8.85 points compared to the control group of 1.93 (p < 0.001) with all slow-learner students experiencing an increase in scores, which confirmed the alternative hypothesis (H₁) that the use of PPP, Pear Deck and Flashcard Factory was effective in improving students' vocabulary. However, qualitative interview data analyzed using thematic analysis revealed mixed results among high-achieving students. Qualitative results showed that students found the vocabulary learning process more interesting and well-structured than the conventional one. However, there were challenges in terms of the pace of learning, as well as too much media that actually disrupted concentration.